Investigation and Analysis of Natural Hazard Impacts on Linear Infrastructure in Southern Kyrgyzstan : Desk and Field Studies Report - World Bank (Washington, DC, 2012)
This report presents the findings of a study of geohazards along 850 km of roads in Southern Kyrgyzstan (KG) and their potential impact on road rehabilitation projects throughout the country. This report presents the findings of a short "fact finding" study on geological hazards (or geohazards) as they relate to ongoing and future planned road rehabilitation projects throughout KG and provides recommendations on activities that could be carried out in KG over the coming years in order to utilize the expertise and data available in country in order to facilitate and improve road design and monitoring/mitigation of geohazard impacts. Section two provides an introduction to the report and section three provides background information behind the study, the objectives and a brief description of the scope of work. Section four describes geohazards in general and details those specifically threatening road developments in KG. Section five describes current road design practices and codes and standards within KG while. Section six discussed briefly the potential economic consequences of geohazards on major roads in KG. Section seven discusses geohard design, mitigation and monitoring of geohazards and presents two examples of detailed geohazard assessment and design and construction techniques developed in other countries. Sections eight and nine present the conclusions and recommendations arising from the study. References are listed in section ten.